1994
DOI: 10.1021/bi00178a019
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Stability and Conformation of Locusta migratoria Apolipophorin III

Abstract: Apolipophorin III (apoLp-III) from the migratory locust, Locusta migratoria, represents the only full-length apolipoprotein whose three-dimensional structure has been solved. In the present study, spectroscopic methods have been employed to investigate the effects of deglycosylation (via endoglycosidase F treatment) and complexation with lipid on the stability and conformation of this protein. Addition of isolated lipid-free apoLp-III to sonicated vesicles of dimyristoylphosphatidylcholine (DMPC) resulted in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
62
1

Year Published

1995
1995
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 32 publications
(46 reference statements)
7
62
1
Order By: Relevance
“…Consistent with the known lability of exchangeable amphipathic apolipoproteins (Edelstein and Scanu, 1980;Weinberg and Spector, 1985), the observed transition midpoints of reduced and oxidized N40C/L90C apoLp-III were 0.25 and 0.43 M GdnHCl, respectively. These values are comparable with those of 0.36 M for WT M. sexta apoLp-III and 0.6 M for L. migratoria apoLp-III (Weers et al, 1994) and suggest that no major structural perturbations in N40C/L90C apoLp-III resulted from the mutations and disulfide bond formation.…”
Section: Evaluation Of Disulfide Bond Formation and Structural Characsupporting
confidence: 72%
“…Consistent with the known lability of exchangeable amphipathic apolipoproteins (Edelstein and Scanu, 1980;Weinberg and Spector, 1985), the observed transition midpoints of reduced and oxidized N40C/L90C apoLp-III were 0.25 and 0.43 M GdnHCl, respectively. These values are comparable with those of 0.36 M for WT M. sexta apoLp-III and 0.6 M for L. migratoria apoLp-III (Weers et al, 1994) and suggest that no major structural perturbations in N40C/L90C apoLp-III resulted from the mutations and disulfide bond formation.…”
Section: Evaluation Of Disulfide Bond Formation and Structural Characsupporting
confidence: 72%
“…In this model, interaction with a lipid surface induces helixbundle opening about hinge loops at one end of the molecule, thereby exposing a continuous hydrophobic surface capable of binding to lipid surfaces. This hypothesis is widely accepted because it is supported by considerable experimental evidence, obtained by using different approaches (9)(10)(11)(12)(13)(14). Using NMR techniques, evidence for a conformational adaptation of apoLp-III was obtained at the amino acid level (24).…”
Section: Resultsmentioning
confidence: 68%
“…A typical 50-ml culture yielded 4 mg of protein with a specific activity of 6 ϫ 10 6 dpm/mg. CD Spectroscopy-A Jasco J-720 spectropolarimeter, interfaced to an Epson Equity 386/25 computer controlled by Jasco software, was used to analyze the ␣-helical content of mutant and wild-type (WT) apoLpIIIs and to monitor temperature-or guanidine hydrochloride-induced denaturation (8). A modified Contin program by Provencher and Glöck-ner (20), which contains poly-L-glutamate as a helical reference standard, was used to estimate the ␣-helical content of the proteins.…”
Section: Methodsmentioning
confidence: 99%
“…The availability of (i) high resolution structural information (7), (ii) biophysical data (8,9), and (iii) a bacterial system for expression of recombinant apoLp-III (10) establishes this as an excellent model system to study structure-function relationships of amphipathic exchangeable apolipoproteins. X-ray crystallography data showed that the lipid-free form of apoLp-III from Locusta migratoria is composed of a bundle of five amphipathic antiparallel ␣-helices (7).…”
mentioning
confidence: 99%